A post‐hoc pooled analysis to evaluate the risk of hypoglycaemia with insulin glargine 300 U/mL (Gla‐300) versus 100 U/mL (Gla‐100) over wider nocturnal windows in individuals with type 2 diabetes on a basal‐only insulin regimen. Issue 2 (2nd October 2018) - Bolli, Geremia B.; Wysham, Carol; Fisher, Miles; Chevalier, Soazig; Cali, Anna M. G.; Leroy, Bruno; Riddle, Matthew C.
Abstract : The EDITION trials in type 2 diabetes demonstrated comparable glycaemic control with less nocturnal and anytime (24‐hour) hypoglycaemia for insulin glargine 300 U/mL (Gla‐300) versus glargine 100 U/mL (Gla‐100). However, the predefined nocturnal window (0:00–5:59 AM ) may not be the most relevant for clinical practice. This post‐hoc analysis compared expansions of the predefined nocturnal interval during basal insulin treatment without prandial insulin. Patient‐level, 6‐month data, pooled from the EDITION 2 and 3 trials and the EDITION JP 2 trial ( N = 1922, basal insulin only) were analysed. Accompanying hypoglycaemia during treatment with Gla‐300 was compared to that during treatment with Gla‐100, using predefined (0:00–5:59 AM ) and expanded (10:00 PM –5:59 AM, 0:00–7:59 AM, 10:00 PM to pre‐breakfast SMPG) windows. Confirmed (≤3.9 mmol/L [≤70 mg/dL]) or severe hypoglycaemic events were reported most frequently between 6:00 AM and 8:00 AM . Windows expanded beyond 6:00 AM included more events than other windows. The percentage of participants with at least one event was lower with Gla‐300 than Gla‐100 in all windows examined. Expanding the nocturnal interval allows better assessment of the risk of hypoglycaemia associated with basal insulin. The risk of nocturnal hypoglycaemia was consistently lower with Gla‐300 versus Gla‐100 using all four windows.